False intimacy: Close-ups and viewer involvement in wildlife films - Bousé, Derek (My University, 2003)
This essay explores the uses of the close-up shot in wildlife films and television shows, raising important questions about the scientific truth value of visual narratives that use this camera technique common in fictional films and television. The close-up shot creates a false intimacy between the human audience and the animal subjects, and among the dangerous results of the technique is the impression that animals have human-like thoughts and emotional responses. While this identification of humans with animals might provide the basis for successful political, economic and social action on behalf of animal welfare, use of the technique raises several important ethical questions regarding the representation of nature and science. © 2003 Taylor & Francis Group, LLC.